2021
DOI: 10.3390/colloids5030038
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Specific and Solvent Effects on PDADMA–PSS Complexation and Multilayer Formation

Abstract: Among various parameters that influence the formation of polyelectrolyte complexes and multilayers, special emphasis should be placed on ion-specific and solvent effects. In our study, we systematically examined the above-mentioned effects on poly(diallyldimethylammonium chloride) (PDADMACl)-sodium poly(4-styrenesulfonate) (NaPSS) complexation in solution and at the surface by means of dynamic light scattering, ellipsometry and atomic force microscopy measurements. As solvents, we used water and water/ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The forming coatings represent by itself a continuous film with on average four and six nm thickness on the glass and PVC substrate, respectively. These results are in good agreement with the data obtained for the PSS/PDADMAC bilayers obtained by the layer-by-layer technique of D. Kovačević et al, and the results of simulation for the multilayers from oligo-PSS and oligo PDADMAC by Sanchez et al [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The forming coatings represent by itself a continuous film with on average four and six nm thickness on the glass and PVC substrate, respectively. These results are in good agreement with the data obtained for the PSS/PDADMAC bilayers obtained by the layer-by-layer technique of D. Kovačević et al, and the results of simulation for the multilayers from oligo-PSS and oligo PDADMAC by Sanchez et al [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a result, an increase in the ionic strength in IPEC solution could induce phase separation. It should be stressed that different ions may have specific affinity to the charged groups of the polyelectrolytes [ 45 , 46 ]. So, the influence of monovalent and bivalent ions’ concentration on the possibility to form water-soluble PSS/PDADMAC complexes was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these growth profiles show the influence of salt concentration and salt type on the growth mechanism and growth rate of a PEM. From Figure a,b, it is evident that increasing salt concentration leads to thicker layer pairs, consistent with previous studies. , This is because salt screens the charges on the polyelectrolytes, weakening their interactions and changing their conformation from an extended chain to a more coil-like conformation. ,,, As for the salt type, NaCl-assembled PSS/PDADMA PEMs grew more slowly than the KBr-assembled ones, Figure . This is because NaCl is more kosmotropic than KBr, so NaCl is less effective at extrinsic charge compensation, leading to the lower growth rate. , This has previously been reported by experiments and simulations alike, in which the more hydrated ions (Na + , Cl – ) generally bind more weakly to the polyelectrolyte charge sites .…”
Section: Resultssupporting
confidence: 87%
“…For ethanol, we conclude that the key to PEM materials scale response is the asymmetric solvation environment, i.e., poor solvation of the ionic groups by ethanol which leads to varying solvent microenvironment around the PEs and consequently enhanced ion condensation. In prior work, this decrease in solvent quality, i.e., increasing the amount of ethanol in assembly solution, has been reported to lead to both film thickness and mass increase. , Here, our QCMD characterization indicated that ethanol addition leads to a decrease of solvent (water + ethanol) in the PEM for PEMs of PSS and PDADMA. The observations indicate that ethanol, because of its polar and apolar ends, is a solvent additive that enables tuning the response by PE chemistry due to the asymmetric solvation character.…”
Section: Discussionmentioning
confidence: 55%